The future of Commonwealth of Independent States : ... will it survive? - Kaul, Triloki Nath (New Delhi : Vikas, 1992)
An Indian diplomat's analysis of Soviet politics in the context of the birth of a new federation of states in place of the Soviet Union.
Includes index.
Bibliography: p. 103.
Keywords: Commonwealth of Independent States